Antioxidant and toxicity activities of kayu manis hutan (Cinnamomum iners Reinw. Ex Blume Laureceae) leaf extracts - Padzil, K.N.M.; Rukayadi, Y.; Abas, F.; Sanny, M.; Abdul-Mutalib, N.A. (Rynnye Lyan Resources, 2024)
Cinnamomum iners Reinw. ex Blume Laureceae which is known in Malaysia as “kayu manis” has a wide range of traditional applications for certain plant parts, including the leaves, bark, and stem and it has pharmacological features, including anti-inflammatory and antibacterial activity. Unfortunately, there is a lack of reports regarding the antioxidant and toxicity activities of ethanolic C. iners crude leaf extracts. The objective of the study was to determine the total phenolic content and its antioxidant activities of ethanolic C. iners crude leaf extracts from two different age maturity, as well as its toxicity activity. The extracts were tested for total phenolic content and its antioxidant activities in terms of 2,2-diphenyl-1-picryllhydrazyl (DPPH) free radical scavenging-and ferric reducing antioxidant power (FRAP) and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) assay. The toxicity assay was tested using brine shrimp (Artemia salina) lethality assay. The total phenolic content of the extracts for young and old leaves C. iners resulted in 248.06±12.77 and 351.11±8.62 mg GAE/g dw, respectively. The DPPH radical scavenging showed results for young and old leaf extracts were IC50 of 31.92 µg/mL and 27.62 µg/mL, respectively. Meanwhile, the value of FRAP for young and old leaf extracts were 8.574±0.21 and 9.155±0.36 TEAC mg/g dw, respectively. The ABTS antioxidant activity for the young and old leaf extracts were 305.23±7.02 and 316.86±8.22 Trolox equivalence mg/g dw, respectively. Based on the toxicity assay, both young and old leaf extracts exhibited LC50 at 19.627 and 13.201 mg/mL, respectively. The findings indicate that C. iners leaves crude extracts have exhibited high total phenolic content and antioxidant activity and the extracts were not toxic against brine shrimp. Thus, C. iners leaf extracts could be developed as potential natural antioxidant agents.